Effect of salivary stimulation on erosion of human and bovine enamel subjected or not to subsequent abrasion: An in situ/ex vivo study - Rios, D.; Honorio, H. M.; Magalhaes, A. C.; Delbem, ACB; Machado, MAAM; Silva, SMB; Buzalaf, MAR (Karger, 2006)
This in situ/ex vivo study evaluated whether saliva stimulated by chewing gum could prevent or reduce the wear and the percent change in microhardness (%SMH) of bovine and human enamel submitted to erosion followed by brushing abrasion immediately or after 1 h. During 2 experimental 7-day crossover phases, 9 previously selected volunteers wore intraoral palatal devices, with 12 enamel specimens (6 human and 6 bovine). In the first phase, the volunteers immersed the device for 5 min in 150 ml of cola drink, 4 times per day (at 8, 12, 16 and 20 h). Immediately after the immersions, no treatment was performed in 4 specimens, 4 other specimens were immediately brushed (0 min) using a fluoride dentifrice, and the device was replaced into the mouth. After 60 min, the remaining 4 specimens were brushed. In the second phase, the procedures were repeated, but after the immersions, the volunteers stimulated the salivary flow rate by chewing a sugar-free gum for 30 min. Changes in wear and %SMH were measured. ANOVA and Tukey's test showed statistical differences (p < 0.05) for the following comparisons. The chewing gum promoted less wear and %SMH. A decreasing %SMH and an increasing enamel wear were observed in the following conditions: erosion only, 60 min and 0 min. The human enamel presented greater %SMH and less wear compared to bovine enamel. The data suggest that the salivary stimulation after an erosive or erosive/abrasive attack can reduce the dental wear and the %SMH.
Keywords: toothbrush abrasion; erosion; dental wear; demineralization; enamel; soft drinks; stimulated saliva